Shaping Ethical Guidelines for Teaching Practice in South African Universities: Building a Policy Framework - (:unkn) unknown (My University, 2024)
Aims: It appears that public South African Universities lack guiding codes of ethics and conduct that specifically guide pre-service teachers’ behaviour and conduct during their teaching practice. To assist South African universities in creating efficient Codes of Ethics (COE) and Codes of Conduct (COC) for teaching practice (TP) as part of their policies, this research sought to establish guidelines for developing a policy framework for ethics in teaching practice.Study Design: A sequential, explanatory, triangulation, mixed-method study was carried out to provide a framework that can inform the development and implementation of such codes.Place and Duration of Study: The study occurred from 2020 – 2021 and included public South African Universities.Methodology: The quantitative content analysis included 14 public universities. Teaching practice coordinators from 9 universities and 55 pre-service teachers (PST) from one Western Cape University participated in the quantitative surveys. 3 teaching practice coordinators and 9 pre-service teachers participated in follow-up interviews.Results: The content analysis revealed a lack of codes of ethics and codes of conduct, specific to teaching practice, at many universities. Most universities seem to apply general codes that were written for the broader university context. Pre-service teachers were found to be unaware of such codes and their content.Conclusion: The lack of codes of ethics and conduct, and students’ awareness thereof, present an array of potential risks for various stakeholders involved in teaching practice. It is expected that pre-service teachers might act more ethically when they have a guiding code to follow. Universities should thus make the codes available on easily accessible platforms and ensure all pre-service teachers are made aware of it before they start teaching practice. Universities could include these codes in course content by letting students discuss and debate it, to
Keywords: African Research